2013
DOI: 10.22610/jebs.v5i7.419
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Student Entrepreneurship in South Africa

Abstract: As rising unemployment levels continually erode job opportunities in South Africa, it is sensible to assume that entrepreneurship would be considered as the next-best career option; however, university graduates show very little interest in becoming entrepreneurs. Having observed this disinterest, South African economic policies have put in place initiatives encouraging youth entrepreneurship; however, these have failed to significantly affect the willingness to engage in entrepreneurial activities. It is agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 14 publications
1
28
0
2
Order By: Relevance
“…Although researchers make many hypothetical commitments, there is a limited number of literature and studies that provide an understanding of how entrepreneurship education, budgeting financial literacy and entrepreneurship education enhance the entrepreneurial performance of SMEs and help with poverty reduction. Some researchers have examined the motivation to become an entrepreneur amongst a sample of black South African entrepreneurs (Chinyamurindi 2016), barriers to student entrepreneurship in South Africa (Shambare 2013), the influence of entrepreneurial orientation on business performance (Matchaba- Hove, Farrington & Sharp 2015), the challenges affecting SMEs in South Africa (Cant & Wiid 2013), the role of SMEs in the economy (Robu 2013), government support for SMEs (Maleka & Fatoki 2016) and the role of open innovation in SMEs (Brunswicker & Van De Vrande 2014). Other matters that researchers have investigated include access to finance for innovative SMEs after the financial crisis (Lee, Sameen & Cowling 2015), elements of e-trade appropriation by SMEs in emerging economies (Rahayu & Day 2015), product lifecycle information management for SMEs (Soto-Acosta, Placer-Maruri & Perez-Gonzalez 2016), groupings for benefit development in SMEs (Kowalkowski, Witell & Gustafsson 2013) and factors that hold back high-growth firms (Lee 2014).…”
Section: Problem Statement and Research Gapmentioning
confidence: 99%
“…Although researchers make many hypothetical commitments, there is a limited number of literature and studies that provide an understanding of how entrepreneurship education, budgeting financial literacy and entrepreneurship education enhance the entrepreneurial performance of SMEs and help with poverty reduction. Some researchers have examined the motivation to become an entrepreneur amongst a sample of black South African entrepreneurs (Chinyamurindi 2016), barriers to student entrepreneurship in South Africa (Shambare 2013), the influence of entrepreneurial orientation on business performance (Matchaba- Hove, Farrington & Sharp 2015), the challenges affecting SMEs in South Africa (Cant & Wiid 2013), the role of SMEs in the economy (Robu 2013), government support for SMEs (Maleka & Fatoki 2016) and the role of open innovation in SMEs (Brunswicker & Van De Vrande 2014). Other matters that researchers have investigated include access to finance for innovative SMEs after the financial crisis (Lee, Sameen & Cowling 2015), elements of e-trade appropriation by SMEs in emerging economies (Rahayu & Day 2015), product lifecycle information management for SMEs (Soto-Acosta, Placer-Maruri & Perez-Gonzalez 2016), groupings for benefit development in SMEs (Kowalkowski, Witell & Gustafsson 2013) and factors that hold back high-growth firms (Lee 2014).…”
Section: Problem Statement and Research Gapmentioning
confidence: 99%
“…This situation has pushed them to avoid the risk as much as they can, in every part of their business. As Shambare et al, (2013) found, fear of failure has been a major psychological situation that needs to be faced by students and is the reason of why they are having less interest to start their business. However, we realize that the context of study and cultural background matter.…”
Section: Discussionmentioning
confidence: 99%
“…Even though it is understood that students have a very big potential to become an entrepreneur, however some studies and research revealed that number of students who actually establish businesses is minimum (Shambare, 2013) and sometimes, their existence cannot be traced. This phenomenon can be found in the data released by each state owned higher education institutions in Padang through their Career Development and Entrepreneurship Unit, which show a very less number of students entrepreneurs in each institution.…”
Section: Introductionmentioning
confidence: 99%
“…The encouragement of entrepreneurship as a possible source of job creation, empowerment and economic dynamism has captured the attention of both researchers and policy makers (Dzisi, 2014).Entrepreneurial activities are not only the incubator of technological innovation, but they also provide employment opportunities (Turker & Selcuk, 2009). In developing countries, however, the university graduates' lack of interest and inability to engage in entrepreneurial activity seems to be the main issue (Shambare, 2013). Scholars have emphasized that entrepreneurship can improve youth livelihood and economic independence in developing countries (Awongbenle & Iwuamadi, 2010;Chigunta, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…One of the main prerequisites for facilitating agricultural graduates' employment is encouraging them to do business (create new businesses, self-employment, intra preneurship and so on). It is therefore sensible to assume that entrepreneurship is a solution to the agricultural and natural resources graduates' unemployment problem (Setiawan, 2014;Shambare, 2013).Graduates who are more mature are more likely to be intended towards entrepreneurship (Sandhu, Sidique & Riaz, 2011). For this reason, further attention should be paid to developing entrepreneurship spirit and abilities of university graduates.…”
Section: Introductionmentioning
confidence: 99%